La educación emocional y su incidencia en el proceso de enseñanza-aprendizaje de los estudiantes del cuarto año básica de la unidad educativa Juan e. Verdesoto del cantón Babahoyo de la provincia de los Ríos - Soria Valdivieso, Ana Luisa (2016)
This research begins with the description of the problem presented by students with little development of emotional education in the Juan E Verdesoto Educational Unit. The theoretical framework describes aspects and factors of emotional intelligence, emphasizing students, teachers and parents based on the theoretical basis of the body such as UNESCO and the OECD, which emphasize the need for comprehensive training that encompasses knowledge that includes competence Emotional, generally full and active human beings, however it is necessary to emphasize that each theory has a different perspective on the capacities to relate with the emotions. A survey was carried out on the total universe of the population, tabulation and interpretation of data provided the recommendations and conclusions, the result obtained gave way to the proposal to solve the problem, which is a didactic guide for teachers and students, which allows the Better development of emotional education in students.